In Vitro Antibacterial Activity and Phytochemical Analysis of Solanum nigrum (Linn.) - An Important Antiulcer Medicinal Plant - Naidu3*, T.M. Sridhar1, P. Josthna2; C.V. (Journal of Experimental Sciences, 2011)
Solanum nigrum (L) is an important herbaceous medicinal plant belongs to Solanacae family. The herb is antiseptic, antidysentric, antidiueretic and is recommended in ayurveda for the management of gastric ulcers. Six solvent extracts from leaf, seed and roots of Solanum nigrum were assayed for in vitro antibacterial activity against pathogenic bacteria such as Bacillus subtilis, Bacillus megaterium, Staphylococcus aureus, klebsiella pneumonia E.coli, Proteous vulgaris, Pseudomonas putrida, and the zone of inhibition were compared with different standard antibiotics. Phytochemical screening of the crude extracts revealed the presence of secondary compounds such as alkaloids, flavonoids, steroids, tainns, and phenols. The organic solvent extracts (ethanol, methanol, ethyl acetate, diethyl ether, chloroform and hexane) of seeds were exhibited strong antibacterial activity against different pathogenic bacteria compared to leaf and root solvent extracts. The ethyl acetate seed extracts of Solanum nigrum exhibited strong activity against Pseudomonas, Proteous vulgaris, Klebsiella (20.5 Ã¢â‚¬â€œ 21.0mm of zone of inhibation). Among different types of extracts tested ethyl acetate seed extract showed lowest MIC values (1.50-4.50 mg/m) against all the bacterial isolates tested.Ã‚Â A lowest MIC value was recorded against pseudomonas putrida, Proteus vulgaris, Klebsiella pneumonia.Ã‚Â